From Answers to Thinking: Students’ Critical Thinking Skills in Solving Problems on Nets of Solid Figures - Riska Amelia; Feri Tiona Pasaribu; Duano Sapta Nusantara (MASI Mandiri Edukasi, 2026)
This study aims to describe students' critical thinking skills in solving mathematical problems, particularly in geometry. The indicators used refer to Facione’s framework, which includes interpreting, analyzing, applying, evaluating, and concluding. This research employs a qualitative descriptive method with ninth-grade students as the research subjects. Data were obtained from students’ written test results and supported by interviews to explore their reasoning processes. The findings reveal that students’ critical thinking skills remain relatively low, especially in evaluation and conclusion. Most students can interpret and apply concepts but have difficulty analyzing problems deeply or verifying their solutions. These results indicate the need to develop innovative teaching materials and learning strategies to enhance students’ critical thinking skills.